Pengembangan Dasar Soft Skill dalam Meningkatkan Kepercayaan Diri Siswa Tingkat Dasar - Nugraha, Enung (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The potential of elementary-level student needs to be developed during the period of character development; thinking and skills need to be fostered and directed. Each student is equipped with abilities and skills that match their interests and talents, so teachers and parents must be able to identify this potential through extracurricular programs. Not all extracurricular activities can improve their soft skills and self-confidence. The activity plan was divided into four meetings with the categorization of participants, namely I to V, assisted by activity managers, namely teachers and students. The results of the activity implementation obtained that students of categories I and II at the first meeting still did not dare to come to the front of the class and speak. However, at the fourth meeting, they showed the courage to come to the front of the class, introduce themselves and speak for 3-5 minutes. Whereas in categories III, IV, and V, there are changes in skills in writing the material to be delivered, dressing techniques, walking techniques, moving one's body parts, managing nervousness, greeting the audience, and the ability to open and close conversations. The implications of developing soft skills through public speaking can increase students' self-confidence.